Principles of chinese criminal procedure - Yue, Liling (Studies in international and comparative criminal law, 2023)
"The book presents a short history and timeline of criminal procedure legislation in China. It first discusses the status of Human Rights Conventions and challenges resulting from human rights standards for Chinese criminal procedural law and practice. It moves on to explore the fundaments of Chinese criminal procedure such as the applicable law found in the Chinese CPC and the Supreme People's Court. The book covers relevant actors in the Chinese Criminal Justice System (judges, prosecutors, police, defence councils) as well as the relationships between them. Actors include crime victims and their role in criminal proceedings. Starting with pre-trial investigation proceedings (extending in particular to coercive measures and discretionary powers of police and prosecutors in the implementation of non-prosecution policies) the book then proceeds with basic principles of the criminal trial, standards of evidence and rules related to conviction and sentencing. Appeal proceedings and the issue of reopening criminal proceedings are also considered. The book finally concludes with questions of enforcement of criminal sentences."--